181k views
0 votes
[tex]cos {}^{4} α+sin {}^{4} α= \frac{1}{4} (3+cos4α)
Prove:


1 Answer

0 votes

Given:


\cos^4 \alpha+\sin^4\alpha=(1)/(4)(3+\cos 4 \alpha)

To prove:

The given statement.

Proof:

We have,


\cos^4 \alpha+\sin^4\alpha=(1)/(4)(3+\cos 4 \alpha)


LHS=\cos^4 \alpha+\sin^4\alpha


LHS=(\cos^2 \alpha)^2+(\sin^2 \alpha)^2


LHS=(\cos^2 \alpha+\sin^2\alpha)^2-2\sin ^2\alpha\cos^2 \alpha
[\because a^2+b^2=(a+b)^2-2ab]


LHS=(1)^2-2(1-\cos^2 \alpha)\cos^2 \alpha
[\because \cos^2 \alpha+\sin^2\alpha=1]


LHS=1-2\cos^2 \alpha+2\cos^4 \alpha

Now,


RHS=(1)/(4)(3+\cos 4 \alpha)


RHS=(1)/(4)[3+(2\cos^2 2\alpha-1)]
[\because \cos 2\theta=2\cos^2\theta -1]


RHS=(1)/(4)[2+2\cos^2 2\alpha]


RHS=(1)/(4)[2+2(2\cos^2 \alpha-1)^2]
[\because \cos 2\theta=2\cos^2\theta -1]


RHS=(1)/(4)[2+2(4\cos^4 \alpha-4\cos \alpha+1)]
[\because (a-b)^2=a^2-2ab+b^2]


RHS=(1)/(4)[2+8\cos^4 \alpha-8\cos \alpha+2]


RHS=(1)/(4)[4+8\cos^4 \alpha-8\cos \alpha]


RHS=1+2\cos^4 \alpha-2\cos \alpha


RHS=1-2\cos^2 \alpha+2\cos^4 \alpha


LHS=RHS

Hence proved.

User Randgalt
by
5.4k points